(untitled) (Analysis in Theory and Applications, 2023)
In this paper we consider the Heckman-Opdam-Jacobi operator ∆_HJ on R^d+1. We define the Heckman-Opdam-Jacobi intertwining operator V_HJ, which turns out to be the transmutation operator between ∆_HJ and the Laplacian ∆_d+1. Next we construct ^tV_HJ the dual of this intertwining operator. We exploit these operators to develop a new harmonic analysis corresponding to ∆_HJ.